Accounting, Chapters 14-26, 27th Edition - Carl Warren (Cengage Learning, 2017)
Gain a solid foundation in accounting to ensure you are prepared for future business courses and the real world with Warren/Reeve/Duchac's market-leading ACCOUNTING, 27E. This edition helps you connect concepts to the bigger picture with features such as the new chapter opening schema that allows you to see how each chapter's specific content fits within the overall framework of the book. A focus on why accounting is important to business and a prosperous society is reinforced throughout with Business Connection features that illustrate how the concept is used in the real world. In addition, the Warren/Reeve/Duchac hallmark accounting cycle coverage provides unmatched foundation so you are prepared to succeed in later chapters.